Pengembangan Modul Menggunakan Autoplay Media Studio 8 di Kelas XI IPS - Novita Sariani; Erna Cahyana (SAP (Susunan Artikel Pendidikan), 2021)
The purpose of this study is to analyze the need for module development Autoplay Media Studio 8, to design an electronic module using Autoplay Media Studio 8, and to test the feasibility of developing modules using Autoplay Media Studio 8. The background of this study is the lack of learning media in electronic form. This study utilized a Research and Development (R&D) type with a modified Borg and Gall development model. The objects of the development were 3 experts and the limited trial class selected was XI IPS 1 class consisting of 5 people, and the usage trial class was XI IPS 3 consisting of 10 people. Data collection tools were observation, interviews, and validation sheets. The results showed that based on the needs analysis, electronic-based learning media was required using Autoplay Media Studio 8. Module development using Autoplay Media Studio 8 utilized 8 stages, namely; potentials and problems, data collection, product design, design validation, design revision, product testing, product revision and usage trials. The feasibility of developing the module Autoplay Media Studio 8 showed a decent category with a score of 79, 87%.